Company man - Finder, Joseph (New York : St. Martin's Paperbacks, 2005)
Nick Conover is the CEO of a major corporation, a local boy made good, and once the most admired man in a company town. But that was before the layoffs. When a faceless stalker menaces his family, Nick, a single father of two since the recent death of his wife, finds that the gated community they live in is no protection at all. He decides to take action, a tragedy ensues - and immediately his life spirals out of control.
National College of Business and Arts
Keywords: Stalking victims -- Fiction; Suspense fiction